Postplacental insertion of IUCD Cu T 380A at transcesarean section does not influence bleeding and infection at puerperial period - Menik Utami; Baksono Winardi (Universitas Airlangga, 2018)
Objective: To determine the difference of the puerperial bleeding and puerperial infection women who had intrauterine contraceptive device (IUCD) T380A insertion at caesarean section compare with women who had caesarean section without IUCD insertion.Materials and Methods: This study was an observasional analytic prospective cohort. Participants allocated to 2 groups : IUCD inserted during cesarean and cesarean with no device inserted. Subject research monitoring at 10 and 40 day of puerperial period.Results: Puerperial bleeding of group with IUCD insertion is 99,309+32,845 ml and group without IUCD is 88,010+30,824 ml, with the analysis test got p=0,085 (p>0,05) means no difference between two groups.Level hemoglobin at post cesarean section (day-0), 10 and 40 day, proportion increasing severity of anemia and duration of lochia rubra were analized and got p>0,05, no difference between two groups. Duration of puerperial bleeding period, median group with IUCD 40 days (25-50) and group without IUCD 30 days (26-45), with analized test got p<0,05. Duration of puerperial bleeding were significantly difference. Proportion of clinical sign puerperial infection 3 (6,4%) of group with IUCD and 2 (4,1%) of group without IUCD, with analized test got p=0,614 (p>0,05), no difference between two groups. Level of leucocyte at post cesarean section (day-0), 10 and 40 day, the difference both two groups was not significant (p>0,05). In this research the difference puerperial bleeding and proportion puerperial infection between two groups (women who had IUCD T380A insertion at caesarean section compare with women who had caesarean section without IUCD insertion) was no significant.Conclusion: Insertion IUCD Cu T 380A postplacental at caesarean section is safety.